2020
DOI: 10.9734/jesbs/2020/v33i1230283
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Management Practices, Organisation Citizenship Behaviour and Turnover Intentions in Public Universities: The Mediating Role of Job Satisfaction

Abstract: Aims: The purpose of this paper was to examine the relationships between human resource management practices (HRMPs) and employee outcomes of organizational citizenship behaviour (OCB) and turnover intentions among employees of Public Universities in Uganda, mediated by job satisfaction. Design/Methodology: The study adopted a cross-sectional, quantitative approach. A sample of 479 academic and non-academic staff was drawn from three public universities in Uganda. SPSS (v20) and AMOS (v20) were used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Without proper training and guidance, employees are less likely to give their best efforts and more likely to engage in unproductive behaviors like social loa ng(Rubel & Rahman, 2018;Deery, 2008;Hughes & Rog, 2008). Talent who has been provided with opportunities for growth within their organization is more likely to share the organization's values and priorities(Khassawneh & Mohammad, 2022a;Tumwesigye et al, 2020; Bagheri et al, 2020;Nzonzo and Chipfuva, 2013).…”
mentioning
confidence: 99%
“…Without proper training and guidance, employees are less likely to give their best efforts and more likely to engage in unproductive behaviors like social loa ng(Rubel & Rahman, 2018;Deery, 2008;Hughes & Rog, 2008). Talent who has been provided with opportunities for growth within their organization is more likely to share the organization's values and priorities(Khassawneh & Mohammad, 2022a;Tumwesigye et al, 2020; Bagheri et al, 2020;Nzonzo and Chipfuva, 2013).…”
mentioning
confidence: 99%
“…This is because without developing talent, their skills will be out of place, leading to poor performance and social loafing, quite apart from ineffectiveness in rendering services to customers (Rubel and Rahman 2018;Deery 2008;Hughes and Rog 2008). It has been shown that talent that received development opportunities from their organisation are likely to be normatively committed to the goals and philosophies of that organisation (Tumwesigye et al 2020;Bagheri et al 2020;Nzonzo and Chipfuva 2013). This implies that the development of talent skills adds value to the organisation in terms of higher productivity orchestrated by talent discretionary behaviour.…”
Section: Talent Development and Sportsmanshipmentioning
confidence: 99%